PENERAPAN METODE DEMONSTRASI TERHADAP PEMAHAMAN SISWA KELAS 1 PADA MATERI BERWUDHU DI MIN 1 KAUR - Manisa Rasti Amanda Putri; Edi Ansyah; Adam Nasution (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to describe the application of the demonstration method in learning ablution procedures at MIN 1 Kaur and to describe students' understanding of ablution procedures after the demonstration method is applied. The problem formulation in this study includes two things, namely how the demonstration method is applied in learning ablution procedures at MIN 1 Kaur and how students' understanding of ablution procedures after the demonstration method is applied. This study uses qualitative descriptive research. Data collection techniques use observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results show that the application of the demonstration method in learning ablution procedures at MIN 1 Kaur has been carried out well and systematically through the stages of planning, implementation, and evaluation of learning. The fiqh teacher has prepared a teaching module, formulated learning objectives, and carried out direct demonstrations by involving students in ablution practices. Learning evaluation is carried out by teachers through practical assessments and written tests. However, the application of the demonstration method still faces several obstacles, such as time constraints, differences in students' understanding abilities, and a large number of students so that the practical evaluation process takes a relatively long time. Students' understanding of ablution procedures after the demonstration method was applied showed quite good results. Students were able to remember the meaning and pillars of ablution, understand the purpose and importance of ablution before prayer, state and apply the sequence of ablution, and begin to analyze errors and evaluate ablution practices with teacher guidance. Thus, it can be concluded that the demonstration method makes a positive contribution to improving students' understanding and skills regarding ablution procedures, although continued habituation, repetition, and teacher guidance are still needed for optimal development of students' understanding.